Westminster Abbey
The structure of this remarkable building , placed in a site at the east and usually occupied by the Lady Chapel, consist of flying transverse arches, on which the pendants behave like keystones, countering the thrust of the vault. The buttresses are in the form of exterior octagonal piers between which the windows form a screen. At the east end of the chapel, five small bays, arranged in an apse, presented problems with the vaulting which were difficult to solve by such a highly geometric system, even though an archway separated the two sections of the vault. Modern tie rods take the horizontal thrust.